2005
DOI: 10.1093/ndt/gfh794
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of vitamin E supplementation on the biochemical and kinetic properties of Tamm–Horsfall glycoprotein in hypertensive and hyperoxaluric patients

Abstract: Background. This study aimed to assess the therapeutic efficacy of oral vitamin E supplementation on the biochemical and kinetic properties of Tamm-Horsfall glycoprotein (THP) in hypertensive and hyperoxaluric patients. Methods. Newly detected hypertensives (n ¼ 200) and stone formers (n ¼ 200) were each subdivided into two groups. One group (n ¼ 100) was administered the antioxidant vitamin E at 400 mg/day given as an oral supplement along with standard therapeutic drugs for hypertension and hyperoxaluria and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 21 publications
4
32
0
Order By: Relevance
“…Although there are no epidemiologic studies showing that vitamin E deficiency is a general phenomenon in chronic hyperoxaluric patients, there is a report showing that low serum vitamin E levels are seen in hyperoxaluric patients (29). These patients have an imbalance in oxidant and antioxidant levels in peripheral blood and can be corrected to near normal levels by vitamin E supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no epidemiologic studies showing that vitamin E deficiency is a general phenomenon in chronic hyperoxaluric patients, there is a report showing that low serum vitamin E levels are seen in hyperoxaluric patients (29). These patients have an imbalance in oxidant and antioxidant levels in peripheral blood and can be corrected to near normal levels by vitamin E supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E is the most potent fat-soluble antioxidant in the chain reaction of removing free radicals, protecting membranes from free radical damage, and preventing lipid peroxidation (3,4). Vitamin E deficiency not only decreases renal antioxidant enzyme protein levels and activities but also enhances the differentiation of monocytes to macrophages (4,29) and superoxide production by increasing NADPH oxidase expression (1). Furthermore, vitamin E deficiency can induce a proapoptotic response in lung cells and sensitize them to additional insult (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In human, the uromodulin is encoded by the UMOD gene, which composed of eleven exons located on chromosome 16p12.3 [1,2]. The primary structure of the polypeptide chain which containing 640 amino acids (aa) with a signal sequence (24 aa) and 8 potential N-linked glycosylation sites [3]. Sequence homology revealed that the protein is may contain N-terminal signal sequence; three epidermal growth factor (EGF)-like domains, the second and third of EGF-like domains contain a calcium-binding motif; a central domain of eight cysteines (D8C) within a cysteine-rich region; a zona pellucida domain is essential for the extracellular protein polymerization into helical filaments; and GPI-anchoring site for integrating the protein with the cell membrane [4].…”
mentioning
confidence: 99%
“…Sequence homology revealed that the protein is may contain N-terminal signal sequence; three epidermal growth factor (EGF)-like domains, the second and third of EGF-like domains contain a calcium-binding motif; a central domain of eight cysteines (D8C) within a cysteine-rich region; a zona pellucida domain is essential for the extracellular protein polymerization into helical filaments; and GPI-anchoring site for integrating the protein with the cell membrane [4]. A key structural feature of the uromodulin is rich cysteine amino acid content (48 cysteines) for creating 24 intrachain disulfide bridges, which critical to construct the correct structure [3]. The biosynthesis of this protein and modification occurs in the rough endoplasmic reticulum (RER) of the TAL cells of the kidney.…”
mentioning
confidence: 99%
See 1 more Smart Citation